A Near‐Infrared Fluorescent Nanosensor (AuC@Urease) for the Selective Detection of Blood Urea. Issue 16 (27th February 2013) - Nair, Lakshmi V.; Philips, Divya S.; Jayasree, Ramapurath S.; Ajayaghosh, Ayyappanpillai
<x xml:space="preserve">Abstract</x> The use of a nanosensor (AuC@Urease) based on an NIR‐emitting gold cluster and urease enzyme selectively detects urea in whole blood. The detection is based on an enzyme‐specific conversion of urea to ammonium ions which facilitates pH‐induced aggregation of AuC, leading to fluorescence quenching. This method does not interfere with urease inactive analytes or the autofluorescence of blood as confirmed by comparable urea levels obtained by AuC@Urease and standard clinical methods within an error limit of ±3%. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>